Assessment of wheat genotypes for yield potential and stress adaptation - Kumar Jatav, Sunil; S Kandalkar, Vasant (Journal of Cereal Research, 2014)
Post-anthesis drought stress is the most important factor affecting wheatproduction adversely in dry-land area. In order to evaluate droughttolerance in bread wheat varieties, an experiment was conductedwith 125 promising genotypes in randomized block design with tworeplications each in no-stress and stress environments. Post-anthesisstress was created after 14 days after anthesis. Different droughttolerance indices viz., stress susceptibility index, relative droughtindex, mean productivity, stress tolerance index, geometric meanproductivity, yield index, yield stability index, drought resistanceindex were evaluated based on grain yield under stress and non-stressconditions. Thirty-one varieties recorded significantly higher grainyield under stress environments along with significant favourablemost of the drought indices viz., SSI, RDI, MP, STI, YI, YSI and DRI.Only 2 genotypes, 31ESWYT-147 and C-306 produced significantlyhigh grain yield in both stress and non-stress conditions. Further,31ESWYT-147 also showed significant favourable values of all droughttolerance indices except GMP, whereas, C-306 showed significantfavorable values only for MP, STI, YI and DRI, respectively. STI andMP showed mostly positive and meaningful genotypic and phenotypiccorrelation with yield in both stress and non-stress environmentsand with other drought tolerance indices. Thus application of bothindices could be appropriate while screening the varieties for droughttolerance. However, according to both STI and MP indices, promisinggenotypes varied differentially for drought tolerance. MP index leadsthe selection towards more efficient genotypes in both stress and nonstressenvironment. Thus screening for drought tolerances could bemade either one or both of these two indices would be more effectivein bread wheat. Drought indices had low heritability and geneticgain which were comparable to yield in stress but higher than yieldin non-stress condition. Hence the improvement for yield potentialunder drought could be achieved through direct selection in stress orscreening through STI and MP indices.